Comparative Analysis of FPGA with Network on Chip Architecture with Routing Techniques - Satish, E. G.; S. B., Rajeshwari; T. R., Vinay; N., Asmathunnisa; S. Naik, Kalpitha; Kallimani, Jagadish S. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The reprogrammable device architectures may bring one-of-a-kind computational abilities to play out the different undertakings. It will help to execution and vitality effectiveness of equipment utilities with the adaptability of software programming and hardware components In a few areas, they are the best way to accomplish the required, constant execution without manufacturing specially coordinated Integrated Circuits (IC). The IC’s usefulness will be fixed and updated amid their operational IC lifecycle for a specific task required. The field of reprogrammable computing device architectures provides a guide to excel information to the body of knowledge Collected in computing architecture and technology, run-time reconfiguration, tools, and applications. The essential focal points of run-time reconfiguration in gadgets are lessened power utilization, equipment reuse, and adaptability.